Effects of chronic hypoxia on semaphorin class 3 expressions in human hippocampal neurons and astrocytes - Jafri Malin, Abdullah (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2018)
Bram requires a continuous supply or oxygen to perform its normal function. Being the largest consumer of oxygen, 1t tS especially sensitive to hypo•ia. a condition in vmich bram receives reduced oxygen Several studies have shown that InJUry to the brain due to loss of oxygen triggers memory loss and causes teaming and memory deficits. Despite many animal studies reported that hypoxia caused neuronal damage in hippocampus which could deficrts learning and memory, but the exact damage caused by chron1c hypoYta on human hippocampal astrocyte has not been analysed yet Our a•m for thiS study ts to understand the cnaractenzation of human hippocampal astrocyte rollovmlg chronk: hypoxia exposure and how the changes varied accordillQ to dtfferent concentration level of oxygen. For the laboratory work. we were using human hippocampal astrocytes cell line and also hypoKia chamber in mimicking the hypoxic condition. Based on lhe preliminary screenmg. almost 80% or cell death occurred after 20 min or hypoxia eKposure at 3% Oxygen and 60% cell death occurred m 15 min of 3% Oxygen. From the data gained. 15 minutes was chosen as the time point and the celJs were exposed to different oxygen percentage (15%. 10%. 5% and 3%). Analysis from Trypan blue viab~ity assay showed abolrt 15% of cells were dead 111 15% oxygen. 25% dead cells m10% oxygen, 48% dead cells in S% oxygen and 65% dead cells in 3% oxygen. For the immunofluorescence Assay, a rel~able marker GFAP was used m order to portray the architecture and morphology of astrocytes cells. Ruorescence scannmg microscope revealed a filamentous and clear nuclear appearance in a control. In contrast. the rupture nudet along with no rigid structure of cell were dtsplayed in chronic hypoKia group, the 3% oxygen eKposure. The control and hypoxia cells also were stained with !he Allnexin V FfTC and then observed under a fluorescence microscope. Cultured astrocytes after hypoxia showed higher expression of nuclei but not in control. Merged between PI and FITC dearly showed the differences of nude1 expression between the control and hypoxia exposed group. Along Wtth that. the HIF-1 sta1ning 'l'r.lS performed to confirm the cell death due to hypoxia e)(posure. Based on the fluorescence microscope viewed. there are dramatiC eKpression of HIF-1 was dl$played in exposed astrocyte cells com;lare to the rorrtrol. For the molecular analysis, we chose several genes such as GAPDH. GFAP. HIF-1a and Bcl2 and ran RT-PCR. General v1ew of human hippocampal astrOC)'1e genomic response to hypoxia was obtained. Key words: Hypox1a. human hlppocarnpal astrocytes. oxygen percentage. cell viability. morphological changes. FITC Annexln V sta1mng. GFAP mal1<er, HIF-1a. GAPDH, Bcl2.